LEGAL REVIEW OF THE SALES OF NON-BPOM CERTIFIED COSMETICS IN E-COMMERCE REVIEWED FROM RI LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION AND BPOM REGULATIONS - Irmanto Brampu; Henry Aspan; Dahlan (RADJA PUBLIKA, 2024)
With the rapid technological developments that are occurring today, it has greatly influenced the technology of the cosmetics industry in making cosmetic products easily, which has led to the proliferation of producers trading in cosmetics without distribution permits and of course this violates consumer rights as regulated by Article 4 and Article 5 of the Law. Law Number 8 of 1999 concerning Consumer Protection and Regulation of the Food and Drug Supervisory Agency Number 17 of 2023 concerning Guidelines for Cosmetic Product Information Documents. The Head of BPOM reiterated that the use of cosmetics without a distribution permit and/or containing prohibited ingredients in cosmetics in accordance with the technical requirements for cosmetic ingredients is very risky for health. Health risks that have the potential to occur due to the use of cosmetics containing prohibited ingredients in cosmetics.